Factors Affecting the Occurrence of Medication Error (ME) in Hospital Pediatrics Unit: Literature Review - Inge Dhamanti; Laela Agrista Devilia (Media Publikasi Promosi Kesehatan Indonesia (MPPKI), 2024)
Introduction: Medication errors do not only occur in adult patients, but can also occur in pediatric patients. Systematic preventive measures are needed to prevent the occurrence of Medication errors in children. This is because pediatric patients have a weaker body than adult patients so that the negative impact of Medication errors will also have a greater effect on pediatric patients than on adult patients. Therefore, it is necessary to identify what factors can lead to the occurrence of Medication errors so that organizational leaders or related parties can determine what intervention actions can be taken to prevent the adverse effects of Medication errors for pediatric patients in hospitals. Objective: The aim of this literature review is to analyze and determine what factors influence the occurrence of medication errors in hospitals, especially in the pediatrics unit. Method: Article searches were conducted through several databases including PubMed, ScienceDirect, and Google Scholar using the keywords "Factor" AND "Medication errors" AND "Pediatrics" AND "Hospital". The total number of articles found was 259 articles, but only 14 articles were relevant to the topic raised. Result: The study was conducted in 24 hospitals in thirteen countries where each of these hospital has several factors that can cause medication errors in pediatric services with the most common factor being the lack of adherence of health workers to procedures or guidelines for drug administration to patients. Conclusion: Medication errors that occur in hospital pediatric services are influenced by 3 factors, namely health human resource factors, patient family factors, and environmental factors.